Use of multimodal glosses in teaching English vocabulary for non-English specialised undergraduates in public university in Nepal - Paudel, Pitambar (Frontiers in Education, 2025)
Knowledge of vocabulary is an essential aspect of language development. Most of the non-English specialised students feel hesitation in communicating in English due to limited vocabulary. Effective vocabulary teaching and learning can be aided by multimodal glosses. In this rationale, this mixed methods participatory action research is intended to investigate the effect of multimodal glosses in improving the English vocabulary of non-English specilised EFL students in a public university in Nepal. The study was conducted in a three-month intervention experiment for an intact class of 60 non-English specilised undergraduates. The data were collected from tests (pre-test, progress-test, and post-test), and interviews. The data were analysed using quantitative statistics (mean, standard deviation, and T-test), and the data from the unstructured interview were analysed descriptively. The overall results revealed that the use of multimodal glosses led to significant improvements in students’ English vocabulary and its use. The findings suggest that the study’s intervention, the use of multimodal glosses, was effective in improving non-English specialised undergraduates’ ability to develop, comprehend, and use English vocabulary. Thus, students and teachers are to be aware of using multimodal glosses contextually to increase, understand, and adopt English vocabulary appropriately.